2020
DOI: 10.1371/journal.pone.0239603
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and determinants of vitamin D deficiency in Indonesian infants at birth and six months of age

Abstract: Background Vitamin D deficiency in infants has been associated with an increased risk of a number of diseases but there are limited data on the prevalence and determinants of vitamin D deficiency from tropical settings with high infant morbidity and mortality. Objective To determine the prevalence and determinants of vitamin D deficiency in infants at birth and at six months of age in Yogyakarta province, Indonesia. Design Serum vitamin D of eligible infants was measured in cord blood at birth and at six month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 50 publications
3
39
1
3
Order By: Relevance
“…Low levels of vitamin D in pregnant women may be one of the causes of low WB BMC in neonates in Indonesia. A study conducted in the same setting as our present study (Yogyakarta) detected vitamin D deficiency in 90% of cord blood samples (24). Two others studies conducted in two different places in Indonesia found that the prevalence of vitamin D deficiency in early pregnancy was very high, namely in Minangkabau: 82.8% and in Jakarta: 99.6% (9, 10).…”
Section: Discussionsupporting
confidence: 59%
“…Low levels of vitamin D in pregnant women may be one of the causes of low WB BMC in neonates in Indonesia. A study conducted in the same setting as our present study (Yogyakarta) detected vitamin D deficiency in 90% of cord blood samples (24). Two others studies conducted in two different places in Indonesia found that the prevalence of vitamin D deficiency in early pregnancy was very high, namely in Minangkabau: 82.8% and in Jakarta: 99.6% (9, 10).…”
Section: Discussionsupporting
confidence: 59%
“…The prevalences of vitamin D insu ciency and de ciency (≤ 20 ng/mL) among unsupplemented breastfed infants in the present study are comparable with those reported in Hong Kong (60%) (13). The prevalences were lower than those reported in India (90%) (14), Taiwan (86.1%) (15), Qatar (83%) (16), and Japan (76.9%) (17) but higher than those in Boston, MA, USA (40%) (18), Kenya (23.4%) (19), and Indonesia (16.7%) (20). The variation in these reported prevalences was likely caused by multiple factors, such as the infants' age, ethnicity, geographical location, and study methodology.…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, an Indonesian study revealed much lower prevalences of vitamin D insu ciency and de ciency than in the present study despite the fact that Indonesia and Thailand are located at similar latitudes in the Southeast Asia region. The authors described the traditional morning sunbathing practice in the study area, which might be one of the factors that contributed to the relatively high serum vitamin D concentration among the infants in this area (20).…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the determinants of vitamin D deficiency at birth and at 6 months has been reported elsewhere [29]. Mothers who spent two hours or more per day outside were less likely to have a newborn with vitamin D deficiency compared to those who spent only 15 minutes or less in the sun [29].…”
Section: Resultsmentioning
confidence: 99%
“…The World Health Organisation (WHO) has called for more research to guide recommendations for the role of vitamin D supplementation to prevent ARIs [27]. A high prevalence of vitamin D deficiency has been reported in children in South East Asia, particularly in newborns [21,28,29]. The prevalence of vitamin D deficiency in Indonesia children aged 2-5 years old was 44% and newborns have been reported at high risk of vitamin D deficiency [29,30].…”
Section: Plos Onementioning
confidence: 99%